2016
DOI: 10.1007/s10973-016-5337-6
|View full text |Cite
|
Sign up to set email alerts
|

Physico-chemical characterization of activated carbon–metal oxide photocatalysts by immersion calorimetry in benzene and water

Abstract: From a commercial activated carbon (AC) and Al 3? , Fe 3? , Zn 2? , SnCl 2 , TiO 2 and WO 4 2in water, three series of AC-metal (hydr)oxide (MO) samples prepared by wet impregnation in two successive steps of soaking at 80 °C and oven-drying at 120 °C (S1) and subsequent heat treatment at 200 (S2) or 850 °C (S3) were characterized texturally by N 2 adsorption at -196 °C and by immersion calorimetry in benzene and water. The mass changes associated with the preparation of the samples are usually stronger for S1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 55 publications
0
3
0
Order By: Relevance
“…This concept has been widely accepted and acknowledged by many researchers. Bogeat et al [44] immersed activated carbon in solutions with various ions to prepare samples coated with metal oxides and found the number and type of hydrophilic groups (functional groups containing oxygen on the activated carbon surface (like hydroxyl, carboxyl, and ketone groups) and coordinating groups and polarized bonds, such as metal-oxygen bonds in metal oxides) in the samples affected their affinity for water. Samples with more hydrophilic groups showed a stronger affinity for water, implying that activated carbon with more hydrophilic groups has higher immersion enthalpies in water.…”
Section: The Influence Of Non-covalent Interactions Between Liquid Mo...mentioning
confidence: 99%
“…This concept has been widely accepted and acknowledged by many researchers. Bogeat et al [44] immersed activated carbon in solutions with various ions to prepare samples coated with metal oxides and found the number and type of hydrophilic groups (functional groups containing oxygen on the activated carbon surface (like hydroxyl, carboxyl, and ketone groups) and coordinating groups and polarized bonds, such as metal-oxygen bonds in metal oxides) in the samples affected their affinity for water. Samples with more hydrophilic groups showed a stronger affinity for water, implying that activated carbon with more hydrophilic groups has higher immersion enthalpies in water.…”
Section: The Influence Of Non-covalent Interactions Between Liquid Mo...mentioning
confidence: 99%
“…When measuring immersion enthalpy as a function of degassing temperature, they observed similar trends in both systems and the immersion heat in non-polar benzene was virtually unaffected by the removal of surface groups during thermal treatment. Acevedo et al [43] chemically activated African palm shells to produce activated carbon and introduced the concept of a "hydrophobic factor," which is defined as the ratio of the immersion enthalpy in benzene to that in water. It was observed that the immersion enthalpies of the activated carbon in benzene and dichloromethane were significantly higher than those in water, which indicates a strong hydrophobic character of the produced activated carbon.…”
Section: The Influence Of Noncovalent Interactions Between Liquid Mol...mentioning
confidence: 99%
“…Stoeckli et al use this technique to characterize the porous structure of a wide variety of carbonaceous materials taking a non-porous carbon black as a reference, assuming that the immersion enthalpy per surface area is proportional to the available surface to the immersion liquid [24].…”
Section: Relationship Between the Enthalpy Of Immersion And The Poroumentioning
confidence: 99%